Challenges of benzodiazepine deprescribing in elderly patients attending primary healthcare - Tinoco, Marlon Silva; Carvalho Júnior, Silvio José Elisei; Ramos, Aline Istefane de Camargos; Rodrigues, Luciana Soares; Pereira, Mariana Linhares; Baldoni, Andre Oliveira (Frontiers in Pharmacology, 2026)
Benzodiazepine deprescribing in older adults is a complex process influenced by systemic, structural, cultural, and individual factors. This qualitative study examined the challenges faced by primary care professionals during the implementation of a supervised deprescribing protocol in a municipality in Minas Gerais, Brazil. Through thematic content analysis, based on Bardin’s methodology and relevant theoretical frameworks for primary care, interviews with community health workers and nurses were analyzed to identify barriers related to structure, process, and outcomes. The main structural barriers included high physician turnover and lack of trust in healthcare professionals. Process-related problems involved failures in information flow and internal coordination. Challenges related to outcomes and patients included resistance due to prolonged use and fear of withdrawal symptoms, limited understanding of the dose reduction process, missed appointments, and lack of home support. These interconnected factors significantly compromised the effectiveness of the intervention. In summary, this study adds that, within the Brazilian Unified Health System (SUS), stable teams, protected time for medication review, network-based psychiatrists, and home-based logistics are prerequisites for effective deprescribing; without these governance conditions, isolated education and protocols tend to fail. These measures are essential to promote treatment adherence, ensure patient safety, and achieve sustainable results in health services that aim to implement deprescribing.